Exploring the Root Causes of Low Household Income among Smallholder Farmers in Kamuli District, Busoga Region, Uganda. - Lubaale, Ronald Gideon; Ocan, Johnson; Adyanga, Francis Akena (Kabale University, 2024)
This study investigated the root causes of low household incomes among smallholder farmers in Kamuli District, Busoga Region, Uganda. Employing a mixed methods approach, the research integrated quantitative and qualitative data collection methods to comprehensively explore the factors influencing household income. The study population comprised 100 smallholder farmers and 20 key informants, totaling 120 respondents. Simple random sampling and purposive sampling were used to select respondents. Data analysis was conducted using SPSS, and reliability statistics indicated a high level of internal consistency among survey items. Qualitative data was analyzed by using thematic analysis. The findings revealed significant challenges faced by smallholder farmers in Kamuli District. These challenges were categorized into agricultural production practices and technologies, institutional factors and market dynamics, and environmental factors and shocks. Limited adoption of modern agricultural practices, poor market access, and climate variability emerged as key impediments to income generation. Possible strategies to address these challenges were identified, including the adoption of modern agricultural practices, investment in training and extension services, infrastructure improvements, access to credit, and establishment of farmer cooperative associations. These strategies aimed to enhance agricultural productivity, market access, and resilience to environmental shocks. The study underscored the interconnectedness of challenges faced by smallholder farmers and emphasized the need for integrated interventions involving technological innovations, institutional reforms, and climate adaptation measures. Collaboration among stakeholders was essential to implement effective solutions and promote sustainable development in agricultural communities. By addressing the root causes of low household income, this study sought to contribute to poverty reduction and food security in Kamuli District and beyond.